Bisnis Dalam Perspektif Islam - Shety Sugiarti Lubis; Sri Anjani; Della Alvionita; Dini Vientiany (Manajemen Kreatif Jurnal, 2025)
Business is a very important thing in the economy, Islam views business as something that must be done but must comply with the rules that have been set in Islam. This article aims to provide information to readers, both prospective entrepreneur students, prospective entrepreneurs so that they can understand in theory how to be an entrepreneur in accordance with Islamic teachings. The research method used in this article is descriptive qualitative. The results of this study are that there are several values ​​that must be applied by business people in doing business, including honesty, justice, and ukhuwah.